2013
DOI: 10.1080/03004430.2013.773991
|View full text |Cite
|
Sign up to set email alerts
|

Children's rights: television programmes aired in Singapore

Abstract: This article focuses on aspects of children's rights as portrayed in television. The results of a six-month research study show analyses of television content of Channel 5, which is the only free-to-air, 24-hour, English-language entertainment channel in Singapore. The results identify the role of television in assisting Singapore to meet its obligations in regard to the Convention on the Rights of the Child. News and advertisements aired on Channel 5 during primetime (between 7 pm and 10 pm) were recorded ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
2
1
0
Order By: Relevance
“…In macro-level decision-making, children's voices remain absent. This finding also corresponds with earlier international studies on the representation of children and their views in media (Kaziaj 2016;Kaziaj & Van Bauwel 2017;Moeller 2002;Ponte 2007;Warrier & Ebbeck 2014). Perhaps, as Barry Percy- warned over 10 years ago, the honeymoon period of children's participation is over.…”
Section: Concluding Discussionsupporting
confidence: 87%
“…In macro-level decision-making, children's voices remain absent. This finding also corresponds with earlier international studies on the representation of children and their views in media (Kaziaj 2016;Kaziaj & Van Bauwel 2017;Moeller 2002;Ponte 2007;Warrier & Ebbeck 2014). Perhaps, as Barry Percy- warned over 10 years ago, the honeymoon period of children's participation is over.…”
Section: Concluding Discussionsupporting
confidence: 87%
“…In macro-level decision-making, children's voices remain absent. This finding also corresponds with earlier international studies on the representation of children and their views in media (Kaziaj 2016;Kaziaj & Van Bauwel 2017;Moeller 2002;Ponte 2007;Warrier & Ebbeck 2014). Perhaps, as Barry Percy-Smith (2006) warned over 10 years ago, the honeymoon period of children's participation is over.…”
Section: Concluding Discussionsupporting
confidence: 86%
“…But one of the most challenging and fundamental shifts in mindset remains necessary – for Singaporeans to think of young children as active persons who are also learning and participating as citizens. Warrier and Ebbeck (2013) have found that while children are frequently present in Singapore’s television advertisements because they capture audience attention, they are largely portrayed as passive subjects receiving nutrition, health and educational interventions. While it is undeniable that children need to grow healthily as biological beings, be cognitively challenged and emotionally secure, the act of reducing a child into a mere health or education project can limit our understanding of the child’s social agency and dynamically shifting needs as he or she interacts with the world in his or her own terms.…”
Section: Introductionmentioning
confidence: 99%